The sources of English teachers’ self-efficacy beliefs : a qualitative study in the South Korean context - Park, Juhee (My University, 2020)
Teachers’ self-efficacy beliefs have been documented to influence various aspects of teaching and learning. Notwithstanding an overall increase of research on teacher efficacy, however, attention to the sources of efficacy beliefs has been relatively insufficient and a majority of the research has been disproportionately carried out in a quantitative manner. Considering the significant impact of teacher efficacy on teachers and students, it is desirable to qualitatively explore the sources of teachers’ self-efficacy beliefs. Investigating high school English teachers seems particularly meaningful in the South Korean context, where English education has become a key agenda in the national policies and experienced considerable changes. Inspired by the initial interest of Bandura’s (1997) hypothesized sources of self-efficacy, the current study employs a qualitative approach through semi-structured interviews. It aims to investigate the sources of high school English teachers’ self-efficacy beliefs in the South Korean context; detect the teachers’ perceived obstacles; and suggest ways to enhance their efficacy beliefs. The findings indicate that the teachers’ self-efficacy is nourished by various information sources including not only the ones postulated by Bandura but also extra sources of information. Among Bandura’s sources, social persuasion is proved to be the strongest to establish their efficacy beliefs. The newly identified sources are English language proficiency and a rapport with students. The study also reveals that the teachers perceived the changes in education, teachers’ multiple responsibilities, lack of collaboration among teachers, their demographic characteristics, different school tracks, and student factors as potential obstacles. Finally, this study suggests there need to be an improvement of in-service teacher training, participation in a teachers’ learning community, and supports from schools and education policy for promoting teachers’ positive self-efficacy beliefs and their professional development.
Keywords: teacher self-efficacy, sources of self-efficacy beliefs, English teachers in South Korea